2016
DOI: 10.1097/sla.0000000000001582
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Kidney Disease and Cardiovascular Mortality After Major Surgery

Abstract: Objective Determine the long-term cardiovascular-specific mortality in patients with acute kidney injury (AKI) or chronic kidney disease (CKD) after major surgery. Summary Background Data In surgical patients, preexisting CKD and postoperative AKI are associated with increases in all-cause mortality. Methods In a single-center cohort of 51,457 adult surgical patients undergoing major inpatient surgery, long-term cardiovascular-specific mortality was modeled using a multivariable subdistributional hazards m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 47 publications
0
37
0
2
Order By: Relevance
“…The adverse effects of AKI persist for years even for those patients who demonstrate partial or even full recovery in renal function by the time of hospital discharge 3,4 . Perioperative AKI is independently associated with a high risk for cardiovascular-specific mortality in diverse patient populations, a risk that is comparable to that observed with CKD 34,35 . In surgical patients who sustain AKI the risk-adjusted average cost for an episode of care was $42,600, compared to $26,700 for patients with no kidney injury 1 .…”
Section: Discussionmentioning
confidence: 73%
“…The adverse effects of AKI persist for years even for those patients who demonstrate partial or even full recovery in renal function by the time of hospital discharge 3,4 . Perioperative AKI is independently associated with a high risk for cardiovascular-specific mortality in diverse patient populations, a risk that is comparable to that observed with CKD 34,35 . In surgical patients who sustain AKI the risk-adjusted average cost for an episode of care was $42,600, compared to $26,700 for patients with no kidney injury 1 .…”
Section: Discussionmentioning
confidence: 73%
“…It has recently been shown that patients with postoperative AKI have high rates of cardiovascular specific mortality after major surgery, similar to that known to occur in patients with CKD. 14 . CKD has been shown to be an independent predictor of in-hospital mortality and morbidity, and worse clinical outcomes are associated with more severe stages of CKD 6, 23-25 .…”
Section: Outcomes - Mortalitymentioning
confidence: 99%
“…Given the increased mortality and morbidity associated with CKD and AKI independently, these effects of these complications are worse when they occur together 6, 7, 14 .…”
Section: Outcomes - Mortalitymentioning
confidence: 99%
“…The nephrologist should be promoting awareness regarding AKI, and should be educating their colleagues about the impact of the institutional and financial burdens of AKI [3539]. These should be repeatedly addressed through educational curricula, clinical rounds and personal communications.…”
Section: Role Of the Nephrologist As Educatormentioning
confidence: 99%